(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
In this article, the optimal conditions for the synthesis of two types of oligomeric corrosion inhibitors, polymethylene diamidophosphate (PDAF-1) and polymethylene thiodiamidophosphate (PTAF-2), based on compounds such as thiourea, urea, and orthophosphoric acid containing nitrogen and phosphorus, as well as their formulas, are determined. At first, (thio)diamidophosphate - PDAF-1 brand corrosion inhibitor was synthesized using urea and orthophosphoric acid in a 2:1 mol ratio at a temperature of 135-140 ºC. The second type of polymethylene thiodiamidophosphate (PTAF-2) corrosion inhibitor was synthesized based on the process of condensation in an aqueous environment at a temperature of 60 ºC, by adding formaldehyde to this obtained compound in a stoichiometric 1:1 mol ratio. The resulting substance is a white solid, non-volatile, the composition of the main component is 98.7%, and other substances - 1.3%. IR-spectra investigated the structure of these two types of corrosion inhibitors. Also, the inhibition efficiency of these corrosion inhibitors was studied by gravimetric and electrochemical methods in corrosive media such as HCl, H2SO4 and NaCl=3%. In addition, the factors affecting the inhibition efficiency, such as the pH of the solution, the duration of time, and the concentration of the inhibitor, were also studied. According to the obtained results, the inhibition efficiency of these corrosion inhibitors was between 95.3 and 97.8%. Also, electron microscopy studied and analysed the protection mechanism of corrosion inhibitors on the steel surface.